2009
DOI: 10.2478/v10022.009-0001-z
|View full text |Cite
|
Sign up to set email alerts
|

Zmiany mechanicznych właściwości skórki owoców pomidora szklarniowego podczas przechowywania

Abstract: This study investigates the effect of the period of storage of greenhouse tomato (Lycopersicon Esculentum Mill) c.v. Admiro on changes in the selected mechanical properties of tomato skin. Changes in the value of Young's modulus and Poisson's ratio were determined in tomato fruit harvested from the maternal plant at the initial phase of skin ripeness, stored in a controlled environment chamber with limited light access at a temperature of 14 o C. A decrease in the value of Young's modulus and Poisson's ratio w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…One is the physical and mechanical properties of whole tomato fruit (Viswanathan et al, 1997;Jahns et al, 2001;Arora and Kumar, 2005;Thiagu et al, 2006;Varshney et al, 2007). Another is the physical and micromechanical properties of different tomato components, such as single tomato cells, epicarp and mesocarp (Blewett et al, 2000;Allende et al, 2004;Wang et al, 2004Wang et al, , 2006Matas et al, 2004Matas et al, , 2005Gloria et al, 2007;Arazuri et al, 2007;Gladyszewska and Ciupak, 2009). The other is the relationship between mechanical properties and injury of tomato (Desmet et al, 2002;Devaux et al, 2005;Linden et al, 2006;Zeebroeck et al, 2007;Li et al, 2010a).…”
Section: Introductionmentioning
confidence: 98%
“…One is the physical and mechanical properties of whole tomato fruit (Viswanathan et al, 1997;Jahns et al, 2001;Arora and Kumar, 2005;Thiagu et al, 2006;Varshney et al, 2007). Another is the physical and micromechanical properties of different tomato components, such as single tomato cells, epicarp and mesocarp (Blewett et al, 2000;Allende et al, 2004;Wang et al, 2004Wang et al, , 2006Matas et al, 2004Matas et al, , 2005Gloria et al, 2007;Arazuri et al, 2007;Gladyszewska and Ciupak, 2009). The other is the relationship between mechanical properties and injury of tomato (Desmet et al, 2002;Devaux et al, 2005;Linden et al, 2006;Zeebroeck et al, 2007;Li et al, 2010a).…”
Section: Introductionmentioning
confidence: 98%
“…Areas found in the research literature where the physical and the mechanical properties has been applied is in two tomato cultivars used for the design and utilization of tomato fruit harvesting robot (Li et al, 2011). Physical and micromechanical properties of tomato fruit's epicarp and mesocarp, which are useful in the production of harvest and post-harvest unit operations robots, were studied by Arazuri et al (2007) and Gladyszewska and Ciupak (2009). Ashtiani et al (2016) investigated some engineering properties of eggplant (cv.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of the physical, mechanical, and thermal properties of agricultural products in the field of the development of automatic processing equipment (Wang, Ma, Fu, Cui, & Majeed, 2020), much research has been done to determine these properties for seeds (Bajpai, Kumar, Singh, Prabhakar, & Meghwal, 2020; Gade, Meghwal, & Prabhakar, 2020; Rokhbin, Azadbakht, & Asghari, 2021; Singh & Meghwal, 2020) grains (Carvalho, Polachini, Augusto, Telis‐Romero, & Bon, 2021; Pohndorf et al, 2018), nuts (Kilanko et al, 2020; Kumar, Prabhakar, Srivastav, & Bhowmick, 2016), kernels (Habibiasr, Mokhtar, Ibrahim, Md Yunos, & Ibrahim, 2020; Razavi & Edalatian, 2012), and fruits (Tan, Tan, Ghazali, & Tan, 2021; Vahedi Torshizi, Khojastehpour, Tabarsa, Ghorbanzadeh, & Akbarzadeh, 2020). Although determining physical properties is more common than mechanical properties, there are reports that investigate the rupture force (Akar & Aydin, 2005; Sirisomboon, Kitchaiya, Pholpho, & Mahuttanyavanitch, 2007), rupture energy (Kılıçkan & Güner, 2008; Sirisomboon et al, 2007), toughness (Lucas et al, 2012; Sirisomboon et al, 2007), hardness (Nwanjika, Onuegbu, & Amaefule, 2017), modulus of elasticity (Mirzabe, Hajiahmad, & Asadollahzadeh, 2021b; Nwanjika et al, 2017), maximum normal contact stress (Mirzabe et al, 2021b; Nwanjika et al, 2017), and Poisson's ratio (Gładyszewska & Ciupak, 2009; Grotte, Duprat, Piétri, & Loonis, 2002) for agricultural crops. However, the conducted literature review showed no conducted research on measuring the physical properties of unripe green grape berries.…”
Section: Introductionmentioning
confidence: 99%